2019
DOI: 10.1016/j.fluid.2019.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Computing solubility parameters of deep eutectic solvents from Molecular Dynamics simulations

Abstract: The solubility parameter (SP) of a solvent is a key property that measures the polarity and quantifies the 'like-dissolves-like' principle, which is an important rule in chemistry for screening solvents for separation processes. It is challenging to experimentally obtain solubility parameters of non-volatile solvents like ionic liquids (ILs), deep eutectic solvents (DESs), and polymers. Here, Molecular Dynamics (MD) simulations have been used to compute the Hildebrand and Hansen solubility parameters of DESs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 110 publications
1
43
0
Order By: Relevance
“…Salehi et al [27] used molecular dynamics simulation to compute the Hilderbrand and Hansen solubility parameters for DESs. Relatively large values were obtained for chlorine chloride based DES (Choline chloride/urea, choline chloride/glycerol, choline chloride/ethylene glycol) compared to molecular solvents and ILs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salehi et al [27] used molecular dynamics simulation to compute the Hilderbrand and Hansen solubility parameters for DESs. Relatively large values were obtained for chlorine chloride based DES (Choline chloride/urea, choline chloride/glycerol, choline chloride/ethylene glycol) compared to molecular solvents and ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Six of such solvents were prepared using different molar ratios of HBA: HBD (1:2 or 1:3) and code named DES1, DES2, DES3, DES4, DES5 and DES6. These DESs were chosen based on their highly polar nature as revealed by Salehi et al [27] and the eutectic feature of the specified molar ratios. Liquid-liquid equilibria (LLE) data for the ternary systems of n-hexane-benzene-DESs were measured at 303 K and 101.3 kPa.…”
Section: Introductionmentioning
confidence: 99%
“…For the other physico-chemical properties there is a great similarity between the molecules. Thus, it can be concluded that the two proposed molecules may have antiemetic activity and the molecule_2 is the best because it has a higher solubility and also the number of HBD and HBA (Salehi et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…hydrogen bond network). As a result, a number of properties of DESs such as the densities [6,33,34,[38][39][40][41], viscosities [6,33,34,[38][39][40][42][43][44], diffusivities [6,34,35,44], ionic conductivities [34,35,40], speed of sound [34,42], and solubilities [16,45,46] are vastly affected, depending on the water content in the mixture.…”
Section: Introductionmentioning
confidence: 99%